Start-up Law - Alexandra Andhov (Edward Elgar Publishing, 2021)
This comprehensive Practical Guide provides direction on the wide array of legal questions and challenges that start-ups face. The Guide features analysis from five jurisdictions that represent a variety of legal traditions across different continents. Expert contributors address key legal issues for technology-based start-ups and entrepreneurs, as well as providing insights into the law and practice of the countries examined.